Internationalisation of a Western Company into Emerging Markets: An Analysis of Philips in China - Lu, Chih-Min/ C-M (2012)
In the recent years, because of the political and economic development, the emerging markets are more stable and more attractive for foreign investors; as a result, more and more international companies seek opportunities to expand their business to the emerging markets in order to maximise the revenues and minimise the costs. This paper examines the factors have the critical influence on a MNE’ entry mode decisions in the emerging markets based on two theories including the internationalisation theory and the transaction cost theory. In the meantime, the paper uses Philips in China as the case study.